Seismic stratigraphy as indicator of late Pleistocene and Holocene sea level changes on the NE Brazilian continental shelf. (October 2016) - Aquino da Silva, André G.; Stattegger, Karl; Schwarzer, Klaus; Vital, Helenice
Abstract: The late Pleistocene Holocene stratigraphic architecture on the northeastern Brazilian continental shelf off the Parnaíba Delta has been explored by high-resolution seismic profiles. The seismic surveys reveal the widespread distribution of incised valleys of different size in offshore continuation of the present-day Parnaiba delta. According to morphology two channel types can be distinguished: U-shaped channels in the eastern part and V-shaped channels in the western part. The stratigraphic successions were grouped into four seismic units separated by different seismic boundaries. The characteristics of the seismic boundaries and internal reflectors of the seismic units were used to distinguish between marine and riverine deposits. The incised-valleys architectural elements were used to link sedimentation processes and variations in base level from late Pleistocene channel avulsion and channel infill in the lowermost course of the paleo-Parnaíba River to marine sediments of the present-day inner shelf. The change of the depositional environments in relation to deglacial sea-level rise is compared to incised valley infills of the Mekong River and Red River systems in Southeast Asia. Graphical abstract: Highlights: High-resolution shallow seismic. Seismic stratigraphy of incised-valleys. Incised-valleys development and infill related to sea level changes. Records of late Pleistocene and Holocene sea level change on the continental shelf. Evolution of the NE South-American Atlantic coast.